Construct validation of the revised Metacognitive Awareness of Reading Strategies Inventory (MARSI-R) and its relation to learning effort and reading achievement - Alamer, Abdullah; Alsagoafi, Ahmad (Studies in Second Language Learning and Teaching, 2023)
Language students apply different strategies to learn a second language (L2), especially when they want to attain proficiency in reading. The aim of the present study was to revisit the validity of the Metacognitive Awareness of Reading Strategies Inventory (MARSI-R) among Saudi students using a new statistical method of confirmatory composite analysis (CCA). Past studies modeled MARSI-R as a common factor and applied confirmatory factor analysis (CFA) to test its validity. However, studies struggled to provide support for the validity of the MASRI-R with each suggesting different model. Instead, we treat the inventory as a composite, meaning that the items in MARSI-R form and define the inventory and not the other way around. We use partial least squared structural equation modeling (PLS-SEM) to allow the composite model to be estimated. The results indicated that the constructs of MARSI-R are better operationalized as composites not common factors as supported through CCA exclusively. After confirming the nature of the inventory, we evaluated the extent to which MARSI-R is related to reading proficiency through the mediational mechanism of motivational intensity (i.e., learning effort). Descriptive statistics illustrated that problem-solving strategies are the most used strategy and that females used the strategies more frequently than their male counterparts. Most importantly, the structural model showed that metacognitive reading strategies only exert an indirect effect on reading proficiency, suggesting that the effect of strategies is mediated by motivational intensity (i.e., learning effort). Thus, motivational intensity seems to be mediator in the relationship between metacognitive reading strategies and reading proficiency. Finally, methodological and educational implications are provided.